L’expérience de la douleur, une activité symbolique ? - Laurent Denizeau (Anthropologie & Santé)
The experience of pain provides an opportunity to consider the relationships between body and mind, sensation and thought, matter and meaning. Supported by a neuroscientific approach, the anthropological understanding of pain emphasizes that our physical experience of the world is embodied in symbolic activity that concerns not only the psyche. René Leriche’s precursory works on the surgery of pain, read through Gerald Edelman’s theory of neuronal group selection, incorporate the symbolic in the biological, without restricting the symbolic to the biological. The body is already an expression of meaning and not only a neutral, objective place receiving meaning from psychic activity, as is claimed by the psychosomatic approach. The body is not reduced to physiology but is inscribed in a system of worldviews. This anthropological reading of the phenomenon of pain suggests another approach of the mind-body issue not in dualist terms of psychosomatics but in terms of physiosemantics (Le Breton, 1995) expressing an embodied human condition.